1998
DOI: 10.1021/jo972027f
|View full text |Cite
|
Sign up to set email alerts
|

Transition State Structure for the Water-Catalyzed Hydrolysis of p-Nitrophenyl Trifluoroacetate in Acetonitrile

Abstract: The neutral hydrolysis of p-nitrophenyl trifluoroacetate in acetonitrile solvent has been studied by varying the molarities of water from 1.0 to 5.0 at 25 degrees C. The reaction is found to be third order in water. The reaction is also third order in D(2)O and in methanol when D(2)O and methanol replace water as the solvent. The kinetic solvent isotope effect is (kH(2)O/kD(2)O) = 2.90 +/- 0.12. Proton inventories at each molarity of water studied are consistent with an eight-membered cyclic transition state m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
(16 reference statements)
3
13
0
Order By: Relevance
“…The first value is very similar to that observed by Venkatasubban et al for p-nitrophenyl trifluoroacetate, a fractionation factor of 0.697 AE 0.005 for a three-proton model. 4 Structure 3 is consistent with the observed effect and we can see that the three hydrogens H a are most likely responsible for the global isotope effect, since the hydrogens H b contribute little or nothing, since they are expected to have a fractionation factor of 1.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…The first value is very similar to that observed by Venkatasubban et al for p-nitrophenyl trifluoroacetate, a fractionation factor of 0.697 AE 0.005 for a three-proton model. 4 Structure 3 is consistent with the observed effect and we can see that the three hydrogens H a are most likely responsible for the global isotope effect, since the hydrogens H b contribute little or nothing, since they are expected to have a fractionation factor of 1.…”
Section: Resultssupporting
confidence: 81%
“…Despite this fact, we believe that the choice of an eightmembered transition state, rather than a six-membered transition state involving two water molecules, is appropriate given that the former has bond angles that accommodate approximately linear hydrogen bonds. 4,27 The water-assistance mechanism in ester hydrolysis has a substantial advantage in comparison with a single water attack. Molecular orbital calculations carried out by Hori et al 10 for the oxygen exchange accompanying the alkaline hydrolysis of methyl acetate showed that the activation barrier for the water-assisted mechanism is lower [3.8 kcal mol À1 (1 kcal ¼ 4.184 kJ)] than that of the hydroxide attack without water assistance (21.8 kcal mol À1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These kinetic features suggest transition state (TS) structures in which many solvent molecules are immobilized and subjected to electrostriction associated with the solvation of developing charges and the trans- There is experimental [16,18] and theoretical [21,22] basis to consider a cyclic atomic array made of one RCO-X molecule and three water molecules, as a more complete picture of the TS complex. Esters of formic acid also undergo neutral hydrolysis, at faster rates compared with the corresponding acetates.…”
Section: Introductionmentioning
confidence: 99%